2018
DOI: 10.3389/fimmu.2018.01148
|View full text |Cite
|
Sign up to set email alerts
|

IP-10 Promotes Blood–Brain Barrier Damage by Inducing Tumor Necrosis Factor Alpha Production in Japanese Encephalitis

Abstract: Japanese encephalitis is a neuropathological disorder caused by Japanese encephalitis virus (JEV), which is characterized by severe pathological neuroinflammation and damage to the blood–brain barrier (BBB). Inflammatory cytokines/chemokines can regulate the expression of tight junction (TJ) proteins and are believed to be a leading cause of BBB disruption, but the specific mechanisms remain unclear. IP-10 is the most abundant chemokine produced in the early stage of JEV infection, but its role in BBB disrupti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
76
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 55 publications
1
76
1
Order By: Relevance
“…In this study, we found that the chemoattractive molecules CXCL10, CCL5, and CCL2 were potently released by the apical compartment upon ZIKV hBLEC infection, suggesting that circulating leukocytes could be attracted to the infected BBB. CXCL10 is emerging as a key inflammatory molecule expressed during neuroinflammatory processes such as autoimmune disorders (e.g., multiple sclerosis [55] or encephalitis [47,56]). It is involved in the recruitment of T cells to the BBB and was proposed to favor inflammatory cell recruitment into the CNS following rabies virus infection (56).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we found that the chemoattractive molecules CXCL10, CCL5, and CCL2 were potently released by the apical compartment upon ZIKV hBLEC infection, suggesting that circulating leukocytes could be attracted to the infected BBB. CXCL10 is emerging as a key inflammatory molecule expressed during neuroinflammatory processes such as autoimmune disorders (e.g., multiple sclerosis [55] or encephalitis [47,56]). It is involved in the recruitment of T cells to the BBB and was proposed to favor inflammatory cell recruitment into the CNS following rabies virus infection (56).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies and our results suggest that ZIKV can directly infect BBB cells but may not have a strong deleterious effect on BBB integrity and that viral particles could be released basolaterally and reach the CNS ( 21 ). Other arboviruses such as WNV and JEV lead to endothelium integrity impairment and inflammatory molecule production that will disrupt BBB integrity and further allow virus CNS access ( 19 , 47 ). Among these cytokines, tumor necrosis factor alpha (TNF-α), IL-1β, transforming growth factor beta (TGF-β), and IL-6 have been shown to modulate BBB permeability by several mechanisms, including downregulation or relocalization of junction proteins such as occludin and ZO-1 ( 48 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous results revealed that JEV itself caused no signi cant damage to the tight junctions of endothelial cells during early infection, which was different to other neurotropic Flaviviridae such as WNV [6,61,62]. On the contrary, the JEV-infected brain supernatant containing MMPs, IL-6, TNF-, CCL-2 and other soluble pro-in ammatory factors, dramatically destroyed the integrity of endothelial cells monolayer in vitro, supporting that the systemic in ammatory response breakdown the BBB during early infection [8,11,63].…”
Section: Discussionmentioning
confidence: 83%
“…While in vivo approaches are useful to understand the systemic viral disease, in vitro models are also useful because they allow studying the molecular mechanisms that govern viral pathogenesis. In this regard, previous approaches have been used to characterize JEV neuroinvasion properties at late times of infection, mainly 24 hpi or later [30, 3335]. However, knowledge relative to the early times of JEV contact with the BBB is poor, if not null.…”
Section: Discussionmentioning
confidence: 99%